Reclaiming Indonesia’s higher education: From human capital to epistemic sustainability - Nadhira Asiyah Arrin (Penelitian Ilmu Pengetahuan Sosial, 2026)
Background: Discussions about the global education paradigm are synonymous with freedom of competition and accountability. This contrasts with the Indonesian education paradigm, which focuses on the concept of harmony between intellectual and moral development. To achieve a balance between the two paradigms, Indonesia’s Merdeka Belajar–Kampus Merdeka (MBKM) reform was launched to promote autonomy, creativity, and innovation in higher education. Yet, beneath its emancipatory discourse, MBKM remains anchored in a human-capital paradigm that measures success through employability rather than moral, ecological, and epistemic reflection. This imbalance reflects a broader crisis in modern education, where freedom is equated with market adaptability instead of ethical responsibility. Methods: This study employs a qualitative conceptual approach, combining critical discourse analysis of MBKM policy documents with theoretical synthesis across decolonial, ecological, and educational thought. The analysis proceeds through three interpretive stages—policy examination, literature synthesis, and theoretical engagement—to uncover the epistemological foundations and "regimes of truth" that govern the current reform. Findings: Three epistemic challenges are identified: epistemic reduction—the confinement of knowledge to technical and measurable forms; moral and ecological detachment—the separation of learning from ethical and environmental consciousness; and managerial autonomy—a paradoxical freedom constrained by neoliberal metrics. These tendencies perpetuate dependency on Western epistemic norms while marginalizing Indonesia’s moral–cultural heritage rooted in budi pekerti and pendidikan merdeka. Conclusion: To transcend this industrial-epistemic paradigm, Indonesian universities must pursue epistemic sustainability—the capacity to sustain and regenerate plural ways of knowing (scientific, local, ethical, and spiritual) in balance. This paradigm repositions education as a moral and civic practice, aligning freedom (merdeka) with responsibility and care. Novelty/Originality of this article: This study introduces epistemic sustainability as an integrative framework linking decolonial, ecological and educational thought, offering a pathway to operationalize the ecology of knowledge within Indonesia’s educational reform.